Competition in Telecoms-Implications for Universal Service and Employment - Petrazzini, Ben A. (World Bank, Washington, DC, 2012)
The author argues that competition in domestic telecommunications markets promotes both universal service and employment in developing countries. Thus, incumbent monopoly operators should be reformed. And since incumbents are subject to increasingly fierce international competition from callback services, Internet phone services, mobile satellite services, and global operators, this reform should happen sooner rather than later.